The Future of Enterprise Systems Integrating Metaverse, Web 3.0, and Extended Reality - Setiawan, Randi; Sulistiani, Heni (LPPM STIKI Malang, 2024)
The convergence of emerging technologies such as the metaverse, Web 3.0, and extended reality (XR) is poised to reshape the landscape of enterprise systems, offering unprecedented opportunities for innovation and user experience. This paper explores the transformative potential of these technologies within the context of enterprise systems, focusing on their implications for user interaction, data management, business processes, and collaboration. We delve into the unique features of each technology and how they can be integrated into existing enterprise systems to enhance user engagement, streamline workflows, and foster new business models. Furthermore, we analyze the challenges and ethical considerations associated with implementing these cutting-edge technologies, highlighting the need for responsible development and ethical guidelines. Ultimately, this paper aims to shed light on the exciting future of enterprise systems as they embrace the transformative power of the metaverse, Web 3.0, and XR, paving the way for a more immersive, interconnected, and innovative business landscape.